Impact of warming on Nostoc colonies (Cyanobacteria) in a wet hummock meadow, Spitsbergen - Elster, J. (Josef); Kvíderová, J. (Jana); Hájek, T. (Tomáš); Láska, K.; Šimek, M. (Miloslav) (Polish Polar Research, 2012)
In order to simulate the warming effects on Arctic tundra, three open-top chambers (OTC) and three control cage-like structures (CCSs) with soil temperature and soil volumetric water content probes were installed in a wet hummock measow in Svalbard in 2009. Prolonged vegetative season was observed in OTCs, however the temperature at hummock base was increased only by 0.3 °C in OTCs compared to CCSs. Photochemical activity and nitrogenase activity of Nostoc colonies did not differ significantly between OTCs and CCSs.